2022
DOI: 10.1021/acs.molpharmaceut.1c00942
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Scutellarin Nanoparticles Augments the Protective Effect against Cerebral Ischemia–Reperfusion Injury in Rats

Abstract: This study investigates the protective effect of poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) loaded with scutellarin (SCU), a flavone isolated from the traditional Chinese medicineErigeron breviscapus (Vant.) Hand.-Mazz., in reducing cerebral ischemia/reperfusion (I/R) injury in vivo. The focal cerebral I/R injury model was established by occluding the middle cerebral artery for 1 h in male Sprague-Dawley (SD) rats. Our SCU-PLGA NPs exhibited an extended in vitro release profile and prolonged bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…These differential metabolites, mainly including phenolic acids, iridoids, and flavonoids, were the active compounds of honeysuckle [ 59 ]. They have active phenolic hydroxyl and are prone to oxidizing and polymerizing to produce some dark compounds under the influence of environmental factors and the action of related enzymes [ 60 , 61 ]. Subsequently, these reactions lead to the darkening or fading of honeysuckle samples.…”
Section: Discussionmentioning
confidence: 99%
“…These differential metabolites, mainly including phenolic acids, iridoids, and flavonoids, were the active compounds of honeysuckle [ 59 ]. They have active phenolic hydroxyl and are prone to oxidizing and polymerizing to produce some dark compounds under the influence of environmental factors and the action of related enzymes [ 60 , 61 ]. Subsequently, these reactions lead to the darkening or fading of honeysuckle samples.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of the infarction was determined using triphenyltetrazolium chloride (TTC) staining in 24 out of the total 38 evaluated studies. Compared to the control groups, the group treated with nanoparticles showed a significant reduction in the infarct area, with the reduction scaling up to 80% depending on the dosage [ 12 , 13 , 16 , 17 , 18 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 40 , 41 , 42 , 43 , 44 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of neurological recuperation was carried out using behavioral metrics in a significant portion of the included studies (68.42%). Several tests were employed in this regard, including the adhesive removal (or sticky tape) test, the beam walk test, the rotarod performance test, the cylinder test, and the grid walking test, to name a few [ 12 , 13 , 15 , 16 , 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, both SCU groups showed a better performance since lower neurological scores were recorded in the diseased rats treated with SCU-PLGA NPs (1.33 ± 0.52) and free SCU (1.83 ± 0.41); the former was lower than the latter. The infarct size of the sick rats treated with SCU-PLGA NPs (19%) was smaller than that of the rats treated with free SCU (27%) [ 68 ]. It was also observed that SCU-PLGA NPs greatly extended the release curve and blood circulation duration of SCU, as well as preventing nerve cell apoptosis, as shown in Figure 4 .…”
Section: Applications Of Plga-based Nanostructures In Drug Delivery A...mentioning
confidence: 99%
“…Data shown as mean ± SD. Adapted with permission from [ 68 ]. Copyright (2022) American Chemical Society.…”
Section: Figurementioning
confidence: 99%